2010
DOI: 10.1158/0008-5472.can-09-3301
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Germ Cell Tumors Display Common MicroRNA Profiles Resulting in Global Changes in Expression of Messenger RNA Targets

Abstract: Despite their extensive clinical and pathologic heterogeneity, all malignant germ cell tumors (GCT) are thought to originate from primordial germ cells. However, no common biological abnormalities have been identified to date. We profiled 615 microRNAs (miRNA) in pediatric malignant GCTs, controls, and GCT cell lines (48 samples in total) and re-analyzed available miRNA expression data in adult gonadal malignant GCTs. We applied the bioinformatic algorithm Sylamer to identify miRNAs that are of biological impo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
308
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(337 citation statements)
references
References 46 publications
25
308
1
3
Order By: Relevance
“…The oncogenic miR-371~373 and miR-302/367 clusters20 (see Figure 3B) are over-expressed in all MGCTs, regardless of age, site, or histologic subtype. 21 Importantly, elevated levels of these miRNAs can be detected in the serum at the time of MGCT diagnosis as well as at relapse, and decline in response to treatment. It is estimated that 70% of non-germinomatous GCTs and 20% of germinomas are secreting.…”
Section: Introductionmentioning
confidence: 99%
“…The oncogenic miR-371~373 and miR-302/367 clusters20 (see Figure 3B) are over-expressed in all MGCTs, regardless of age, site, or histologic subtype. 21 Importantly, elevated levels of these miRNAs can be detected in the serum at the time of MGCT diagnosis as well as at relapse, and decline in response to treatment. It is estimated that 70% of non-germinomatous GCTs and 20% of germinomas are secreting.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is suggested that specific miR are involved in the maturation of mouse gonocytes to pre-spermatogonia (McIver et al, 2012a,b). Most recently, detection of miR in serum of GCC (adult and pediatric) patients has been reported from two independent groups (Belge et al, 2012, Murray and Coleman, 2012, Palmer et al, 2010. This opens novel possibilities for the diagnosis and follow-up of GCT patients.…”
Section: Mirnas In the Development Of Germ Cells And Gccmentioning
confidence: 95%
“…GCT display micro-RNA profiles similar to embryonic stem cells, and these embryonic miRNA types are already highly upregulated and detectable in pre-invasive GCNIS cells [97]. Interestingly, the characteristic miRNA profiles are similar in GCT that arise in children and adults, and are detectable in all histological subtypes and components, except teratoma [21,98,99]. This specific TGCT profile, which was detected by several groups independently from each other, includes a high level of miR-371-3 cluster, miR-302 and miR-367.…”
Section: Traces Of Gct In Blood: Classical Biochemical Markers and MImentioning
confidence: 99%